Thermal and structural study of new hydrated salts of the drug norfloxacin with pyrazinoic acid with increased solubility - de Paula Costa, Giovanna [UNESP]; Ferreira, Patrícia Osório [UNESP]; Isquibola, Guilherme [UNESP]; dos Santos, Juliana Guedes [UNESP]; Caires, Flávio Junior [UNESP] (Springer Nature, 2025)
This work reports on the thermal, structural and spectroscopic study of new Norfloxacin salts. Norfloxacin is an antibiotic for the treatment of infectious diseases in the gastrointestinal and urinary tracts. However, it has low aqueous solubility which may lead to adverse effects on the patient due to incomplete metabolism in the body. Pharmaceutical salts are multicomponent crystalline solids formed by the interaction between drug and counterion and are effective in improving the physicochemical properties. Stoichiometric ratios of precursors were used to obtain new salts using the mechanochemical and slurry method with environmentally safe solvents. Single crystals were obtained from slow evaporation of the solvent, and the structure was solved revealing a new tetrahydrate salt. Hirshfeld surface analysis was used to investigate the intermolecular interactions and forces involved in the crystal structure. The powdered compounds were investigated by simultaneous thermogravimetry and differential thermal analysis, differential scanning calorimetry-microscopy, powder X-ray diffraction and infrared spectroscopy. The characterization revealed the reproducibility of the tetrahydrate salt and identified a new monohydrate salt. Complete dehydration of both salts obtained revealed a new anhydrous salt, confirmed by the analyses mentioned above. The evaluation of the solubility of the compounds was performed and showed better solubility of the salts with the order: anhydrous salt > monohydrate > tetrahydrate > Norfloxacin. This work demonstrated the importance of thermal investigation in pharmaceutical salts to differentiate, quantify and transform different compounds, aiming at obtaining new stable materials with better physicochemical properties for drugs with low solubility.